Factorial validity and measurement invariance of a self-reported scale of paradoxical leadership behaviours: evidence from sport industry leaders - Bourke, Matthew; Cairney, John; Richard, Veronique; Mulcahy, Samantha; Moos, Chris; Dopson, Sue (Frontiers in Psychology, 2025)
IntroductionOrganisational leaders across all sectors are often faced with a dynamic, unpredictable and complex business landscape. Understanding leadership style is integral to optimising leadership and organisational culture and performance. One such leadership style that warrants further investigation is Paradoxical Leadership. This study examines the factorial validity and measurement invariance of a self-report version of the Paradoxical Leadership Scale (PLS) among a diverse sample of sport industry leaders. These sport industry leaders (n = 345) provided a platform to explore paradoxical leadership in a seldom-examined sector.MethodsParticipants were recruited through an online campaign, partnering with the sports media company, SportsPro. Factorial validity of the self-reported PLS was examined using Exploratory Structural Equation Modelling (ESEM), and measurement invariance testing was conducted using Multiple Indicator Multiple Causes (MIMIC) modelling across demographic and contextual factors.ResultsResults confirmed the second-order five factor model as the best fit, with partial deviations in item loadings but maintaining overall structural integrity. The scale showed full invariance across managerial levels, experience, gender, and regions, with partial invariance across age groups, indicating its robust applicability.DiscussionThis is the first study to explore the factorial validity and measurement invariance of a modified, self-report scale measuring paradoxical leadership behaviours in a diverse sample of sport leaders. The findings support the use of this scale for both research and practical application in this context. Further research applying this scale across sectors is recommended.